A Review on Diabetes: Current and Future Perspectives - Chauhan, Anushree; Mishra, Ganesh Prasad; Gupta, Surbhi (Current Indian Science, 2024)
Diabetes Mellitus (DM) is a metabolic syndrome that gradually leads to chronic microvascular or macrovascular complications. There are 2 types of DM: Insulin-dependent diabetes, commonly called type I DM, is an organ-specific autoimmune disorder that destroys the body’s pancreatic β cells, causing insulin deficiency, and can be treated through insulin replacement therapy. Non-insulin-dependent diabetes mellitus, or type II DM, is caused by pancreatic cell dysfunction that affects a person’s ability to use insulin and can be treated with oral hypoglycaemics. Recent investigation confirms that combination therapy of metformin (biguanides), sodium-glucose co-transporter-2 (SGLT2) inhibitors, and Dipeptidyl Peptidase-4 (DPP-4) inhibitors not only reduces HbA1c glucose dependently but also provides better sustained glycaemic stability with good tolerability in comparison to monotherapy. Multi-particulate drug delivery provides targeted drug administration with high bioavailability and compressed dosage administration. In this review analysis, an effort has been made to explore the pathophysiology of type II DM and the importance of combination therapy using microspheres for the delivery of drugs for the management of type II DM.
Keywords: Microspheres